The effect of tax knowledge and tax awareness on taxpayer compliance with e-filing as a moderating variable - Sonny, Sonny; Firmansyah, Amrie; Trisnawati, Estralita (WIM Solusi Prima, 2025)
This study investigates the influence of tax knowledge and tax awareness on taxpayer compliance, with e-filing examined as a moderating variable. Data were collected through questionnaires from 96 individual taxpayers registered at the North Batam Pratama Tax Office (KPP Pratama Batam Utara). The research employed a quantitative associative approach with a causal design, and the data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3. The results reveal that tax knowledge has a negative effect on taxpayer compliance, while tax awareness has a positive effect. Furthermore, e-filing moderates these relationships in different ways: it weakens the negative effect of knowledge by simplifying reporting procedures, but it also reduces the direct influence of awareness as compliance becomes more associated with technological convenience. These findings underscore the relevance of the Theory of Planned Behavior in explaining compliance behavior, while also highlighting the role of technology in reshaping compliance dynamics. Future studies are encouraged to incorporate broader behavioral and institutional factors, and policymakers are advised to strengthen tax education, awareness campaigns, and the reliability of e-filing infrastructure.